Business networking and sustainability of small rural business: Mediating effects of entrepreneurial orientation - Mohamad, Mohd Amin; Chin, Othman (Growing Science, 2018)
This study aims to examine the entrepreneurial orientation (EO) of the Small Rural Business (SRB) entrepreneurs in Malaysia by taking Business Networking (BN) as the antecedent.BN is used to explain the influence of EO as a mediator and its’ consequences towards SRB Business Sustainability (BS).The survey method was employed in this study and the data was analyzed using Structural Equation Modelling (SEM) multivariate data analysis.Based on the SEM analysis,it can be concluded that in this study,the relationship between BN and BS was not mediated by EO.However,BN has direct effect towards EO.Moreover,EO and BN were significant as predictors towards BS.Size,age and technology of SRB were used as control variables in this study.